Federiquito el sapo - Greydanus, Rose.; Garcia, Tom. (Mahwah, N.J. : Troll Associates, 1981)
Story about a frog who learns that each animal makes its own unique sound.
Spanish version of: Freddie the frog.
Keywords: Spanish language -- Reading (Elementary); Toads -- Fiction; Spanish language -- Vocabulary